Turkish families with juvenile motor neuron disease broaden the phenotypic spectrum of SPG11. (October 2015) - Iskender, Ceren; Kartal, Ece; Akcimen, Fulya; Kocoglu, Cemile; Ozoguz, Aslihan; Kotan, Dilcan; Eraksoy, Mefkure; Parman, Yesim G.; Basak, Ayse Nazli
Abstract : Objective: Identification of causative mutations in 3 consanguineous families (with 4 affected members) referred to our center with young-onset motor neuron disease and overlapping phenotypes resembling autosomal recessive juvenile amyotrophic lateral sclerosis (ARJALS) and autosomal recessive hereditary spastic paraplegia (ARHSP). Methods: Patients have a slowly progressive motor neuron disease with upper and lower motor neuron dysfunction. There is distal muscle weakness and atrophy associated with pyramidal signs. Whole-exome sequencing was performed on the patients and the unaffected parent samples to identify disease-causing mutations. Variants were prioritized according to their predicted pathogenicity and their relevance to the clinical phenotypes. Results: Five distinct homozygous mutations within the SPG11 gene were identified, 3 of which were novel and truncating: c.7155T>G/p.Tyr2385Ter, c.2250delT/p.Phe750Leufs*3, and c.1966_1967delAA/p.Lys656Valfs*11. The copresence of 2 distinct homozygous missense variations was observed in 2 families: c.6224A>G/p.Asn2075Ser and c.7132T>C/p.Phe2378Leu. The segregation of these variations in the family members was validated by Sanger sequencing. Conclusions: Four patients with juvenile-onset motor neuron disease with consanguineous parents were found to carry homozygous mutations in the SPG11 gene. Our findings confirm the overlapping phenotypes of SPG11 -based ARJALS and ARHSP, indicating that these 2 entities may be the extreme phenotypes of the same disease continuum with many common features. This, in turn, confirms the difficult differential diagnosis of these 2 diseases in the clinic.